HYPOLIPIDEMIC ACTIVITY OF HARITAKI (TERMINALIA CHEBULA) IN ATHEROGENIC DIET INDUCED HYPERLIPIDEMIC RATS - V. Maruthappan; K. Sakthi Shree (Wolters Kluwer Medknow Publications, 2010)
Haritaki (Terminalia chebula) family Combretaceae is an important plant used traditionally for medicinal purposes. It is component of the classic Ayurvedic combination called "Triphala". Hyperlipidemia was induced by treated orally with atherogenic diet. In atherogenic diet induced hyperlipidemic model, the rats receiving treatment with Haritaki showed significant reduction in total cholesterol, triglycerides, total protein and elevation of high density lipoprotein cholesterol. Haritaki was found to possess significant hypolipidemic activity. The results also suggest that Haritaki at 1.05 and 2.10 mg/kg b.wt. concentrations are an excellent lipid-lowering agent.